UPAYA PESANTREN MUHAMMADIYAH KWALA MADU LANGKAT DALAM MENINGKATKAN LIFE SKILL SANTRI - Muhibuddin Muhibuddin; Asrul Asrul; Sefrila Manda Sari; Hamdani Hamdani (Jurnal Anifa: Studi Gender dan Anak, 2022)
The challenges of Islamic boarding schools in the era of globalization and modernization are changing rapidly because of the urgency of these challenges. Although the intensity and form of pesantren are not the same as one another, this reality impacts the existence of the continuity of the pesantren, the role and achievement of the goals of the pesantren, as well as the public's view of this institutionalized education. This type of research uses a qualitative approach with a case study type at the Modern Muhammadiyah Islamic Boarding School in Kuala Madu Langkat, North Sumatra. Data collection techniques through observation, interviews, and documentation, as well as using qualitative analysis techniques. The results of this study conclude that the efforts of the Modern Muhammadiyah Islamic Boarding School Kwala Madu Langkat, North Sumatra, in improving life skills are pretty reasonable, namely, by carrying out three stages, namely 1) habituation, 2) assignment, 3) training with language development programs such as giving vocabulary, muhadtsah, muhadara, as well as activities that support extracurricular activities, namely Tahfidz al-Qur'an, calligraphy, sports, sewing and so on. These three stages are carried out with the characteristics and abilities of the students who want to be developed.